The enhancement of lexical competence of students on B2 level - Mukhtarov Mukhiddin Mansur o’g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article reviews the notion of lexical competence and semantic competence. Since the president of Uzbekistan issued a decree on popularizing and further development of learning foreign languages, to be precise English.